1999
DOI: 10.1128/mcb.19.5.3466
|View full text |Cite
|
Sign up to set email alerts
|

Specific Acetylation of Chromosomal Protein HMG-17 by PCAF Alters Its Interaction with Nucleosomes

Abstract: Nonhistone chromosomal proteins HMG-14 and HMG-17 are closely related nucleosomal binding proteins that unfold the higher-order chromatin structure, thereby enhancing the transcription and replication potential of chromatin. Here we report that PCAF, a transcription coactivator with intrinsic histone acetyltransferase activity, specifically acetylates HMG-17 but not HMG-14. Using mass spectrum sequence analysis, we identified the lysine at position 2 as the predominant site acetylated by PCAF. Lysine 2 is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 52 publications
1
80
0
4
Order By: Relevance
“…Post-translational modifications of HMGN2 have been shown to have a profound effect on its biochemical and biological functions. Phosphorylation of the serine residues located at the nucleosome binding domain could affect HMGN2 binding affinity with nucleosomes (17,36) and acetylation of HMGN2 by p300/CBP-associated factor (PCAF) also reduces the binding affinity with nucleosome (16), implying the possible role of SUMOylation in HMGN2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-translational modifications of HMGN2 have been shown to have a profound effect on its biochemical and biological functions. Phosphorylation of the serine residues located at the nucleosome binding domain could affect HMGN2 binding affinity with nucleosomes (17,36) and acetylation of HMGN2 by p300/CBP-associated factor (PCAF) also reduces the binding affinity with nucleosome (16), implying the possible role of SUMOylation in HMGN2.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of HMGN pro-teins to nucleosomes can be altered by HMGN modification. Equilibrium dialysis experiments with reconstructed nucleosomes and non-acetylated HMGN2 showed that acetylated HMGN2 had lower binding affinity for nucleosomes, suggesting that acetylation may function to loosen the interaction between HMGN2 and nucleosomes (16). Phosphorylation of HMGN2 also serves to abolish the interaction of HMGN2 with its chromatin targets (17).…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%
“…Acetylation of HMGN2 leads to a weakening of its nucleosome binding ability (40,41). Binding of HMGN1/N2 to nucleosomal cores inhibits the PCAF mediated acetylation of histone H3 (41). It is however not known how the HMGNs get recruited in a specific gene.…”
Section: Classification Of Nonhistone Substrates Of Hats and Hdacsmentioning
confidence: 99%
“…Quite interestingly, though p300 can acetylate both HMGN1 and N2 at multiple sites (40), PCAF specifically acetylates HMGN2 (41). Acetylation of HMGN2 leads to a weakening of its nucleosome binding ability (40,41). Binding of HMGN1/N2 to nucleosomal cores inhibits the PCAF mediated acetylation of histone H3 (41).…”
Section: Classification Of Nonhistone Substrates Of Hats and Hdacsmentioning
confidence: 99%
See 1 more Smart Citation